Bilingual virtual toolkit ‘let’s twist’ - Nazir, Faridah; Kasdi, Abdul Manan; Wang, Leong Boon; Ramli Mohd Yunos, Amril Zalha (Centre for Teaching and Learning (CTL) International Islamic University Malaysia (IIUM, 2018)
Tongue twisters are sequence of words, short phrases or short stories that repeat problem sounds or the same group of sounds to make them difficult to pronounce when saying them quickly. Tongue twisters are a fun way to help children improve their speaking skills and pronunciation. Realising this, a Bilingual Virtual Toolkit ‘Let’s TwiST’, which is a dual language TwiST kit, is produced to help pupils, not only to practise their pronunciation in English and Malay Languages, but also to assist teachers and pupils in writing their own TwiSTs. This kit is user-friendly as anyone can utilise it in any language skill activities. The kit also provides the users with various types of sources for TwiST activities which includes the online and offline materials. Therefore, The Bilingual Virtual Toolkit ‘Let’s TwiST’ will enable both teachers and pupils to create fun and interesting TwiSTs any time for varied language activities in an enjoyable, non-threatening and positive learning environment.